Evaluation of host resistance in brinjal to Pseudomonas wilt in Chotanagpur - S. KUMAR, J.P. SHARMA and (Indian Phytopathology, 2002)
Pseudomonas wilt (Pseudomonas solanacearum Smith) is one of the most destructive and wide spread bacterial diseases in India affecting a variety of solanaceous crops and causes severe losses (25-75%) in yield. Data on field resistance in egg plant is there, but the elite lines developed by the breeder need confirmation for resistance in different zones. Hence the lines from Project Directorate of Vegetable Research (P.D.V.R.) were tested for resistance.